1984
DOI: 10.1111/j.1748-5827.1984.tb03427.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of positive contrast vaginourethrography as a diagnostic aid in the bitch

Abstract: The contribution of vagino‐urethrography to the diagnosis of disorders of the lower urogenital tract in 123 bitches was evaluated. It was found to be particularly valuable in animals with urinary incontinence, vaginal discharge, dysuria and physical vaginal abnormalities. Determination of vaginal volume in 69 bitches has enabled a dosage of contrast medium to be suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 9 publications
0
14
2
Order By: Relevance
“…A radiographic exposure was made during injection as soon as full opacification of the urethral lumen and streaming of contrast medium into a moderately distended urinary bladder 8 were seen. Dogs were placed in dorsal recumbency with their catheters still in place.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A radiographic exposure was made during injection as soon as full opacification of the urethral lumen and streaming of contrast medium into a moderately distended urinary bladder 8 were seen. Dogs were placed in dorsal recumbency with their catheters still in place.…”
Section: Methodsmentioning
confidence: 99%
“…Marked (ie, diameter less than a third of the vaginal diameter) nondistensible stenosis of the vestibulovaginal junction has been reported in 7 of 23 normal bitches who did not have clinical evidence of urogenital abnormalities in a study that evaluated positive contrast vaginourethrography as an diagnostic aid in the bitch. 8 This finding suggests that what has been called vestibulovaginal stenosis actually may be a normal variation in the dog and may have been an incidental finding in some dogs with lower urinary tract or reproductive disease. It is difficult to assign clinical significance to 1 anatomical defect when several conformational abnormalities or predisposing factors occur in the same patient (eg, pelvic bladder, recessed vulva, sphincter mechanism incompetence, hyperadrenocorticism, diabetes mellitus) with lower urinary tract disease.…”
mentioning
confidence: 99%
“…In a study 4 of 22 dogs, the author contended that vestibulovaginal stenosis was the cause of clinical signs that included vulvar dermatitis and urinary incontinence. 1,8 In our study, dogs with vestibulovaginal ratios that indicated severe stenosis (< 0.20) were more likely (P = 0.02) to have unsuccessful treatment than were dogs with ratios > 0.20, regardless of other factors. In another report, 7 it is suggested that stenosis may lead to recurrent UTIs or chronic vaginitis but is probably not an important cause of urinary incontinence.…”
Section: Discussionmentioning
confidence: 50%
“…1,2 Abnormalities diagnosed with this technique include ectopic ureters, diverticuli, pelvic bladder, neoplasia, and vestibulovaginal stenosis. Urinary incontinence, vaginitis, stranguria, and recurrent urinary tract infections (UTIs) are common conditions.…”
mentioning
confidence: 99%
“…12 The vestibulovaginal ratio can then be calculated to determine the severity of the stenosis. As part of the physical examination of female dogs with recurrent urinary tract infections, digital vaginal palpation should be considered to assess for the presence of vestibulovaginal stenosis.…”
Section: Discussionmentioning
confidence: 99%